(untitled) (Mustansiria Dental Journal, 2018)
Squamous cell carcinoma is the most common malignant tumor of oral mucosa. Oral cancer is one of the prevalent cancers of the body and is the most common cause of the death, in Iraq little is written regarding the occurrence of oral cancer. Clinical details of 129 (80 males and 49 females) patients with oral squamous cell carcinoma were collected from the Institute and Hospital of Radiotherapy And Nuclear Medicine Center in Baghdad during the period 2003-2006.The aim of the current study is to find out the prevalence of oral cancer in different governorates of Iraqi patients in relation to gender, age and site. The highest prevalence was observed in tongue 72 (55.81%) while the lowest prevalence was found in the floor of the mouth 5 (3.87%). The age groups 51–60 years were highly affected by squamous cell carcinoma 45(34.88%), while the lowest affected age groups were <10 years and 11-20 years 1 (0.77%). Baghdad governorate had the highest prevalence of oral squamous cell carcinoma 53(41.08%) .